TINJAUAN ATAS PENGARUH PENERBITAN SP2DK TAHUN PAJAK 2016 TERHADAP LAPORAN KEUANGAN TAHUN 2021PADA PT TRI PURA INDAH PERSADA - Erica Novita Sari (2022)
Sources of state income from natural resources and human resources in the form of taxes. Tax collection is the main choice as an alternative source of state financing. Taxes are contributions paid by the people to the state which are included in the state treasury and are regulated in laws that are bound and coercive. One of the methods used by the Directorate General of Taxes in achieving the target of tax revenues is by supervising taxpayers through the issuance of a letter requesting an explanation of data or information (SP2DK). SP2DK is issued by an Account Representative. The causes of PT Tri Pura Indah Persada to receive SP2DK is because of the difference in business circulation which is smaller than the submission of the mass tax return, the difference in the value of the corporate income tax interest cost with the DPP value related to the article 23 and article 4 paragraph (2) of the Periodic Income Tax Return. The difference in salary costs in the SPT PPh 21, there is a tax invoice that should not have been issued because it has been canceled. After the issuance of SP2DK, of course there will be an effect of recording in financial statements related to taxes reported by taxpayers who receive SP2DK. Keywords: Taxes, Taxpayers, SP2DK, Effect of Issuance, Financial Statements